2005
DOI: 10.1002/art.21268
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor receptor I from patients with tumor necrosis factor receptor–associated periodic syndrome interacts with wild‐type tumor necrosis factor receptor I and induces ligand‐independent NF‐κB activation

Abstract: Objective. To investigate the molecular consequences of expressing mutated forms of tumor necrosis factor receptor I (TNFRI) as found in patients with TNFR-associated periodic syndrome (TRAPS).Methods. We cloned and expressed full-length wild-type (WT) and T50K and P46L variants of TNFRI using a new tightly regulated doxycycline-dependent expression system. This system enabled the study of molecular interactions between these receptors at both physiologic and pathophysiologic levels of expression.Results. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 37 publications
5
45
0
3
Order By: Relevance
“…However, one explanation could be a negative feedback on CD45RB expression by the low molecular weight isoform detected in SLE B cells. In this regard, there is evidence that alternative isoforms exert negative feedback on the expression/function of other isoforms of the protein in question (44)(45)(46). Of relevance to our study, this observation could imply that the CD45 found in the LRs is an isoform different from CD45RB.…”
Section: Discussionmentioning
confidence: 64%
“…However, one explanation could be a negative feedback on CD45RB expression by the low molecular weight isoform detected in SLE B cells. In this regard, there is evidence that alternative isoforms exert negative feedback on the expression/function of other isoforms of the protein in question (44)(45)(46). Of relevance to our study, this observation could imply that the CD45 found in the LRs is an isoform different from CD45RB.…”
Section: Discussionmentioning
confidence: 64%
“…It has been postulated that TNF release stimulated by UPR activation may then signal through the wild-type TNFR1, generating an autocrine positive feedback loop enhancing TNF production [21,22]. It is also conceivable that mutant intracellular TNFR1 may still stimulate TNF production by activation of their intracellular death domains independent of receptorligand binding, particularly as this domain is rarely mutated in TRAPS.…”
Section: Autoinflamamatory Diseases Linked To Disorders In Protein MImentioning
confidence: 99%
“…DNA sequences of all constructs were verified by sequencing at the Genome Centre, William Harvey Research Institute. Plasmid DNA was purified from E. coli DH5α using Qiagen maxiprep kits (Crawley, UK) and was transiently transfected into 293T cells using the calcium phosphate co-precipitation method as previously described [9]. For biological assays, 293T cells were incubated in 10% heat inactivated FBS in DMEM (Invitrogen) (with 100U/ml penicillin, 100µg/ml streptomycin and 2mM L-glutamine) and the supernatant collected 48 hours posttransfection.…”
Section: Construction and Expression Of Latent Cytokines With Human Lapmentioning
confidence: 99%